Mathematical Process Skills of Middle School Students under Direct Instruction and Ethnomathematics - Lucy Astagina Putri; Kamid Kamid; Khairul Anwar (MASI Mandiri Edukasi, 2026)
Mathematics instruction at the junior high school level in Indonesia is often teacher-centred, which may limit the development of students’ mathematical process skills. This study investigates the impact of Direct Instruction and ethnomathematics-based Problem-Based Learning (PBL) on the mathematical process skills of seventh-grade students. A quantitative quasi-experimental design with a nonequivalent control group was employed, involving 64 students at SMP Negeri 7 Kota Jambi, divided into an experimental and a control group. Data were collected through pretests and posttests assessing skills such as observing, classifying, identifying relationships, calculating, and communicating mathematical ideas. Data analysis included descriptive statistics and the Mann–Whitney U test. The results revealed that students receiving ethnomathematics-based PBL exhibited greater improvement in mathematical process skills than their peers taught via Direct Instruction, indicating that integrating local cultural contexts within a PBL framework can enhance mathematical reasoning, problem-solving, and active engagement in learning.